BIPA Learning Based on Ecolinguistics on the Listening and Speaking Skills of BIPA Students in Vietnam - Aninditya Sri Nugraheni; Aninda Aji Siwi; Anjar Sulistiawati (Yayasan Keluarga Guru Mandiri, 2024)
Current environmental problems need to be a significant concern, but there has not been much research that integrates ecolinguistics in BIPA learning. This research aims to describe the implementation of ecolinguistic-based BIPA learning on listening and speaking skills for Vietnamese BIPA students. This research used a mixed-method research approach with a sequential exploratory strategy. The research was conducted in Vietnam with subjects of 26 BIPA students and BIPA program teachers. The research instruments used were observation sheets, interview guides, questionnaires, and documentation. Qualitative data is analyzed descriptively through data collection, data reduction, data presentation, and drawing conclusions. The validity of qualitative data is carried out using technical triangulation. Quantitative data was analyzed descriptively using the JASP 0.17.1.0 application. The research results show that ecolinguistic-based BIPA learning in Vietnam uses scientific strategies through traditional Indonesian food. The media used is flash cards. There is a positive correlation between the listening and speaking skills of BIPA students in Vietnam. Apart from the learning innovations that have been carried out, there is also a need for innovation in BIPA teaching materials based on pluricultural competencies so that BIPA students learn not only Indonesian but also Indonesian culture.